A sulfide solid-state electrolyte and a method for preparing the same

CN122696774BActive Publication Date: 2026-10-09江苏智泰新能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611186566.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-09
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

在多晶体系中,晶界电阻往往占总阻抗的30%-60%,严重制约了电解质膜的整体离子电导率

Benefits of technology

(1)本发明通过预制具有纳米晶-非晶互连结构的晶界离子通道调控组分,并使其在复合烧结后于Li6PS5Cl型硫银锗矿主晶相的晶粒接触区域形成含碘硫代磷酸盐晶界调控相。该晶界调控相能够填充部分晶粒间隙并改善颗粒间有效接触,从而降低电解质片总阻抗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122696774B_ABST
    Figure CN122696774B_ABST
Patent Text Reader

Abstract

The application discloses a sulfide solid electrolyte and a preparation method thereof. The sulfide solid electrolyte is prepared from raw materials including the following components by mass: 100 parts of lithium sulfide, 94-100 parts of diphosphorus pentasulfide, 33-39 parts of lithium chloride and 4-10 parts of a grain boundary ion channel regulating component; the grain boundary ion channel regulating component has a nanocrystal-amorphous interconnection structure composed of beta-Li3PS4 nanocrystal domains and amorphous interdomain phases located between adjacent nanocrystal domains. The regulating component is distributed in the grain contact area of a Li6PS5Cl type argyrodite main crystal phase, forms an ion transmission channel between adjacent grains, reduces the grain boundary resistance and improves the lithium ion conductivity. The lithium ion conductivity is not lower than 3.5 mS / cm under the condition of 25 DEG C and 300 MPa pressure retention, the lithium ion conduction activation energy is not higher than 0.32 eV, and the sulfide solid electrolyte can be applied to a full solid-state lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state battery materials technology, specifically to a sulfide solid electrolyte and its preparation method. Background Technology

[0002] All-solid-state lithium batteries replace traditional liquid electrolytes with solid electrolytes, fundamentally eliminating safety hazards such as leakage, evaporation, and combustion associated with liquid electrolytes. They also possess higher energy density potential and a wider operating temperature range, making them a core direction for next-generation energy storage technology. Among various solid electrolyte systems, sulfide solid electrolytes have attracted widespread attention due to their high room-temperature lithium-ion conductivity, good mechanical deformation capability, and low grain boundary resistance.

[0003] Among sulfide solid electrolytes, Li6PS5Cl-type silver-germanium sulfide-structured electrolytes have become a key system for research and application due to their high room-temperature ionic conductivity (typically 1-3 mS / cm), good lithium stability, and relatively simple synthesis process. Li6PS5Cl is synthesized by introducing Cl into the Li3PS4 framework structure. - Partially replaces S 2- The Li6PS5Cl electrolyte forms a sulforaphane-germanium ore structure, providing three-dimensional lithium-ion transport channels within the crystal lattice and exhibiting high bulk ionic conductivity. However, the practical application of Li6PS5Cl electrolytes still faces the following technical challenges.

[0004] First, the grain boundary resistance is relatively high. During the film formation process of polycrystalline Li6PS5Cl powder, the physical contact area between grains is limited. The grain boundary regions exhibit disordered atomic arrangement, chemical segregation, and space charge layer effects, resulting in lithium ions needing to overcome a high energy barrier when crossing the grain boundaries. In polycrystalline systems, grain boundary resistance often accounts for 30%-60% of the total impedance, severely limiting the overall ionic conductivity of the electrolyte membrane.

[0005] Second, the ionic conductivity needs further improvement. The room temperature ionic conductivity of existing Li6PS5Cl electrolytes is mostly in the range of 1.5-3.0 mS / cm, which is still far from meeting the actual requirements of high-power all-solid-state batteries. Halogen doping and element substitution can improve the bulk conductivity to some extent, but they are difficult to effectively improve the ion transport performance in the grain boundary region.

[0006] Third, the electrode-electrolyte interface compatibility is insufficient. The solid-solid interface contact resistance between the sulfide electrolyte and the positive electrode active material is relatively high, making the interface prone to side reactions and structural degradation during charge-discharge cycles, leading to a decrease in battery cycle life. In addition, the interface stability between the lithium metal anode and the sulfide electrolyte also needs further improvement.

[0007] Fourth, sulfide solid electrolytes are extremely sensitive to moisture in the air. Li6PS5Cl undergoes hydrolysis upon contact with water vapor, generating toxic hydrogen sulfide gas, while the ionic conductivity of the electrolyte decreases significantly. This necessitates that the preparation and processing of sulfide solid electrolytes be carried out in a highly inert atmosphere, increasing process complexity and production costs.

[0008] To address the aforementioned issues, existing technologies have explored methods to improve grain boundary ion transport by introducing second-phase materials into sulfide electrolytes. For example, adding oxide nanoparticles (such as Li₂ZrO₃ and Al₂O₃) can reduce grain boundary resistance to some extent, but the oxide phase itself has extremely low ionic conductivity, and excessive addition can dilute the overall conductivity of the electrolyte. Another approach uses lithium sulfide-phosphorus sulfide glass-ceramics as grain boundary modification layers, but the room-temperature ionic conductivity of these materials is relatively low (typically below 1 mS / cm), and their uniform distribution at grain boundaries and interfacial bonding with the main crystalline phase still require optimization. Other approaches use elemental doping modification (such as replacing Cl sites with Br or P sites with Ge or Sn) to improve ionic conductivity and electrochemical stability, but elemental doping often introduces new chemical components, increasing the complexity and synthesis difficulty of the material system, and the improvement effect of doping on grain boundary resistance is limited. Therefore, how to provide a sulfide solid electrolyte with low grain boundary resistance, high ionic conductivity, and excellent interfacial compatibility remains a technical problem that needs to be solved by those skilled in the art. Summary of the Invention

[0009] The purpose of this invention is to provide a sulfide solid electrolyte and its preparation method. By introducing a grain boundary ion channel regulating component with a specific nanocrystalline-amorphous interconnect structure into the grain contact region of the main crystal phase of Li6PS5Cl type silver sulfide germanium ore, ion transport channels are formed between adjacent grains, thereby reducing grain boundary resistance and improving the overall lithium-ion conductivity and electrochemical cycle stability of the electrolyte.

[0010] To achieve the above objectives, the technical solution adopted by the present invention is: a sulfide solid electrolyte, which is made from raw materials comprising the following parts by weight: 100 parts of lithium sulfide, 94-100 parts of phosphorus pentasulfide, 33-39 parts of lithium chloride, and 4-10 parts of a grain boundary ion channel regulating component.

[0011] Furthermore, the grain boundary ion channel regulating component is made from raw materials comprising the following parts by weight: 100 parts lithium sulfide, 160-166 parts phosphorus pentasulfide, 8-18 parts lithium iodide, and 2-6 parts lithium phosphate.

[0012] Furthermore, the grain boundary ion channel regulating component has a nanocrystalline-amorphous interconnect structure composed of β-Li3PS4 nanocrystalline domains and an amorphous intergranular phase located between adjacent β-Li3PS4 nanocrystalline domains; the amorphous intergranular phase is a Li2S-P2S5 amorphous glass phase containing lithium iodide and lithium phosphate, with lithium iodide and lithium phosphate co-distributed in the amorphous intergranular phase.

[0013] Furthermore, the sulfide solid electrolyte has a Li6PS5Cl type silver-germanium sulfide main crystal phase, and the grain boundary ion channel regulating component forms an iodine-containing thiophosphate grain boundary regulating phase after composite sintering. The grain boundary regulating phase is distributed in the grain contact region of the Li6PS5Cl type silver-germanium sulfide main crystal phase.

[0014] Furthermore, the sulfide solid electrolyte is made from raw materials comprising the following parts by weight: 100 parts lithium sulfide, 95-100 parts phosphorus pentasulfide, 33-37 parts lithium chloride, and 5-8 parts grain boundary ion channel regulating components.

[0015] Furthermore, the grain boundary ion channel regulating component is made from raw materials comprising the following parts by weight: 100 parts lithium sulfide, 160-166 parts phosphorus pentasulfide, 10-15 parts lithium iodide, and 3-5 parts lithium phosphate.

[0016] Furthermore, the purity of the lithium sulfide is not less than 99.9%; the purity of the phosphorus pentasulfide is not less than 99.9%; and the purity of the lithium chloride, lithium iodide, and lithium phosphate is not less than 99.5% respectively.

[0017] Furthermore, the particle size D of the grain boundary ion channel regulating component... 50 Its thickness is 0.5-3.0 μm, and its specific surface area is 3-15 m². 2 / g; the particle size D of the sulfide solid electrolyte 50 The particle size is 1-8 μm, and the particle size D 90 No larger than 15μm.

[0018] Furthermore, in the X-ray diffraction pattern of the sulfide solid electrolyte, the Li6PS5Cl type silver-germanium sulfide phase is the main crystalline phase, and β-Li3PS4 related crystalline phase characteristics and amorphous scattering background are present; the lithium-ion conductivity of the sulfide solid electrolyte measured at 25℃ and 300MPa is not less than 3.5mS / cm, and the lithium-ion conduction activation energy is not higher than 0.32eV.

[0019] A method for preparing a sulfide solid electrolyte includes the following steps: S1. In an argon-protected environment with a water content not exceeding 0.1 ppm and an oxygen content not exceeding 0.1 ppm, weigh the raw materials according to the following proportions: 100 parts by mass of lithium sulfide, 160-166 parts by mass of phosphorus pentasulfide, 8-18 parts by mass of lithium iodide, and 2-6 parts by mass of lithium phosphate. Add the raw materials and zirconium oxide grinding media to a closed ball mill container, control the mass ratio of grinding media to raw materials to be 25:1-35:1, and ball mill at 400-500 r / min for 8-12 h to obtain a mechanically activated mixture. S2. The mechanically activated mixture is placed in an argon atmosphere and heated to 200-230°C at a heating rate of 2-5°C / min and held at that temperature for 3-5 hours. Then, it is cooled to below 80°C at a cooling rate of 1-3°C / min, ground, and passed through a 200-mesh sieve to obtain a grain boundary ion channel regulating component with a β-Li3PS4 nanocrystalline-amorphous interconnection structure. S3. Weigh the raw materials according to 100 parts by mass of lithium sulfide, 94-100 parts by mass of phosphorus pentasulfide, 33-39 parts by mass of lithium chloride and 4-10 parts by mass of the grain boundary ion channel regulating component. Add the raw materials and zirconium oxide grinding media into a closed ball mill container, control the mass ratio of grinding media to raw materials to be 30:1-40:1, and ball mill at 450-600 r / min for 10-18 h to obtain a solid electrolyte precursor. S4. The solid electrolyte precursor is loaded into a covered boron nitride crucible, and the boron nitride crucible is placed in a sealed stainless steel reaction vessel. The sealed stainless steel reaction vessel is evacuated and purged with argon gas 2-3 times. Finally, the vacuum is evacuated to an absolute pressure not higher than 50 Pa, and then argon gas with a purity not lower than 99.999% is introduced to a gauge pressure of 0.02-0.05 MPa. The temperature is increased to 470-520℃ at a heating rate of 2-4℃ / min and held for 4-8 hours. The temperature is then cooled to below 80℃ at a cooling rate of 1-3℃ / min to obtain a sinter containing the main crystalline phase of Li6PS5Cl type silver sulfide germanium ore. S5. In the argon-protected environment, the sintered material is ball-milled with zirconia grinding balls at 250-400 r / min for 1-3 h, and then passed through a 100-300 mesh sieve to obtain the sulfide solid electrolyte. The ball-milling time in each of the above steps includes the total time, including pause times.

[0020] Furthermore, the ball milling in step S1 is carried out in a cycle of continuous ball milling for 20-30 minutes and stopping ball milling for 10-15 minutes. During the ball milling process, the outer wall temperature of the sealed ball milling container is maintained at 20-45℃.

[0021] Furthermore, the ball milling in step S3 is carried out in a cycle of continuous ball milling for 25-35 minutes and stopping ball milling for 10-15 minutes. During the ball milling process, the outer wall temperature of the sealed ball milling container is maintained at 20-50℃.

[0022] Further, step S4 includes: first heating to 250-300℃ at a heating rate of 2-4℃ / min and holding at that temperature for 1-2 hours, then heating to 470-520℃ at a heating rate of 2-3℃ / min and holding at that temperature for 4-8 hours; the sulfide solid electrolyte obtained in step S5 is sealed and packaged in a dry argon atmosphere with a dew point not higher than -60℃.

[0023] The product in question involves a sulfide solid electrolyte that can be used in the manufacture of electric vehicles and other motor vehicles, excluding the manufacture of related components for fuel cell vehicles.

[0024] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention modulates the composition by prefabricating grain boundary ion channels with nanocrystalline-amorphous interconnection structures, and then forming an iodine-containing thiophosphate grain boundary regulating phase in the grain contact region of the main phase of Li6PS5Cl type silver sulfide germanium ore after composite sintering. This grain boundary regulating phase can fill part of the grain gaps and improve the effective contact between particles, thereby reducing the total impedance of the electrolyte sheet.

[0025] (2) The vibrational signal of phosphate groups and the broadened peak of thiophosphate coexist in the Raman spectrum. The EDS results show that iodine is relatively enriched in the inter-domain phase of amorphous state and the grain boundary region of composite electrolyte, indicating that phosphate groups and iodine-containing components participate in the formation of inter-domain phase and grain boundary regulation phase. This compositional feature is conducive to maintaining the free volume and structural stability of amorphous network.

[0026] (3) The present invention employs a two-step preparation process. First, a grain boundary ion channel regulating component with a nanocrystalline-amorphous interconnect structure is prepared by low-temperature heat treatment (200-230℃). Then, it is mixed with the main crystalline phase raw material and sintered at high temperature (470-520℃) to form the Li6PS5Cl main crystalline phase and the iodine-containing thiophosphate grain boundary regulating phase. In addition, the two-stage heating process in step S4, which first preheats at 250-300℃ for 1-2 hours, is beneficial to the diffusion and reaction homogenization of the components in the precursor, thereby improving the overall lithium-ion conductivity and electrochemical stability. Attached Figure Description

[0027] Figure 1 This is the Raman spectrum of the grain boundary ion channel modulation component in Example 1 of the present invention.

[0028] Figure 2 This is a transmission electron microscope image of the grain boundary ion channel regulation component in Example 1 of the present invention.

[0029] Figure 3 This is a transmission electron microscope image of the grain boundary structure of the sulfide solid electrolyte in Example 1 of the present invention.

[0030] Figure 4 This is a cross-grain boundary elemental line scan curve of the sulfide solid electrolyte of Example 1 of the present invention. Detailed Implementation

[0031] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] The present invention will be further described in detail below with reference to specific embodiments and comparative examples. The raw material information used in each embodiment and comparative example is as follows: Lithium sulfide (Li₂S), purity 99.99%, particle size D 50 The particle size is 5.2 μm; phosphorus pentasulfide (P2S5), purity 99.99%, particle size D 50 The grinding media consisted of 12.5 μm particles; lithium chloride (LiCl), 99.99% purity, anhydrous powder reagent; lithium iodide (LiI), 99.95% purity, anhydrous powder reagent, vacuum dried before use; lithium phosphate (Li3PO4), 99.9% purity, anhydrous powder reagent, vacuum dried before use; and lithium bromide (LiBr), 99.99% purity, anhydrous powder reagent. Zirconia grinding media were 5 mm diameter zirconia grinding balls. The ball milling equipment was a planetary high-energy ball mill. All weighing, mixing, grinding, heat treatment, and sieving operations were performed in an argon-protected glove box with a water content not exceeding 0.1 ppm and an oxygen content not exceeding 0.1 ppm, and the glove box dew point was not higher than -70°C. Ball milling in sealed grinding jars and heat treatment in sealed reaction vessels or argon-purified quartz tubes were carried out in corresponding equipment outside the glove box. Materials were kept sealed or under argon protection throughout the transfer process.

[0033] The term "β-Li3PS4 nanocrystalline-amorphous interconnect structure" as used in this specification refers to a structure in which crystalline thiophosphate features and broadened background coexist in Raman spectroscopy, and nanocrystalline domains with lattice contrast and inter-domain regions without clear lattice contrast are interconnected in the representative field of view of TEM. The domain size and inter-domain phase thickness mentioned in this document are only used to illustrate the relative structural features in the representative field of view and are not intended to limit the overall particle size distribution of the powder.

[0034] Example 1

[0035] Preparation of grain boundary ion channel modulating components: Weigh out 50.0g of lithium sulfide, 81.5g of phosphorus pentasulfide, 6.25g of lithium iodide, and 2.00g of lithium phosphate, totaling 139.75g. Add the above raw materials and zirconia grinding balls to a 4L sealed zirconia ball mill jar. The mass ratio of zirconia grinding balls to raw materials is 30:1, i.e., the mass of grinding balls is 4192.5g. After sealing the ball mill jar, remove it from the glove box and install it on a planetary ball mill. Set the ball mill speed to 450r / min and ball mill continuously for 25min, then stop for 12min, for a total ball milling time of 10h (including downtime). During the ball milling process, maintain the outer wall temperature of the ball mill jar between 25-38℃. After ball milling, return the ball mill jar to the glove box and remove the mixture to obtain a mechanically activated mixture.

[0036] The mechanically activated mixture was transferred to a quartz glass tube and heated to 215°C at a rate of 3°C / min under an argon atmosphere, held at that temperature for 4 hours, and then cooled to room temperature (approximately 25°C) at a rate of 2°C / min. The heat-treated product was ground for 5 minutes in a glove box and passed through a 200-mesh standard sieve (75 μm pore size) to obtain the grain boundary ion channel regulating component. Laser particle size analysis showed that the particle size D50 of this grain boundary ion channel regulating component was 1.8 μm, and the specific surface area (BET method) was 8.5 m². 2 / g. TEM observation revealed that nanoscale β-Li3PS4 crystal domains were interconnected with several nanometer-scale inter-domain regions lacking clear lattice contrast in the representative field of view; EDS surface scanning analysis showed that iodine was relatively enriched in the inter-domain regions.

[0037] Preparation of sulfide solid electrolytes: Weigh out 50.0 g of lithium sulfide, 48.75 g of phosphorus pentasulfide, 17.50 g of lithium chloride, and 3.25 g of the aforementioned grain boundary ion channel regulating component, for a total mass of 119.50 g. Add the above raw materials and zirconia grinding balls to a 4 L sealed zirconia ball milling jar. The mass ratio of zirconia grinding balls to raw materials is 35:1, i.e., the mass of the grinding balls is 4182.5 g. After sealing the ball milling jar, remove it from the glove box and install it on a planetary ball mill. Set the ball milling speed to 525 r / min and ball mill continuously for 30 min, then stop for 12 min, for a total ball milling time of 14 h (including the stop time). During the ball milling process, maintain the outer wall temperature of the ball milling jar between 28-45℃. After ball milling, return the ball milling jar to the glove box, remove the mixture, and obtain the solid electrolyte precursor.

[0038] The aforementioned solid electrolyte precursor was loaded into a covered boron nitride crucible, which was then placed in a sealed stainless steel reaction vessel. The sealed stainless steel reaction vessel was evacuated to an absolute pressure of 30 Pa, and then filled with 99.999% pure argon gas until the gauge pressure reached 0.035 MPa. The reaction vessel was placed in a tube furnace, heated to 495 °C at a heating rate of 3 °C / min, held at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 2 °C / min. The sintered material was ball-milled in a glove box at 325 r / min for 2 h, and passed through a 200-mesh standard sieve (75 μm aperture) to obtain sulfide solid electrolyte powder. Laser particle size analysis showed that the particle size D50 of this sulfide solid electrolyte was 3.5 μm, and the particle size D90 was 12.3 μm. XRD analysis revealed that the Li6PS5Cl type silver-germanium sulfide phase was the main crystalline phase, with a small amount of β-Li3PS4 related crystalline phase characteristics and an amorphous scattering background.

[0039] like Figure 1 As shown in the figure, at approximately 450-470cm -1 The highest intensity and somewhat broadened characteristic peak appears at approximately 390-420 cm⁻¹. -1 A distinct shoulder peak forms at this point, primarily corresponding to the vibration of the PS bond in the thiophosphate structure; approximately 170-280 cm. -1 Low wavenumber peaks and lattice vibrations within the range and PS4 3- Related to group bending vibration, approximately 930-950 cm -1 The weak peak at this point can be attributed to phosphate group vibrations. The broadening of the main peak, its asymmetric shape, and the preservation of crystalline characteristics support the coexistence of β-Li3PS4 nanocrystalline domains and Li2S-P2S5-based amorphous regions containing iodine and phosphate groups.

[0040] like Figure 2 As shown in the figure, multiple nanocrystalline domains with lattice contrast can be observed. The nanocrystalline domains are connected and surrounded by inter-domain regions with shallow contrast and no clear lattice contrast, forming continuous or semi-continuous nanocrystalline-amorphous interconnect features. This structure is beneficial for using β-Li3PS4 nanocrystalline domains to provide lithium-ion conduction sites and improving interparticle wetting and interface adhesion through amorphous regions.

[0041] like Figure 3 As shown in the figure, the large gray area represents the main grains of Li6PS5Cl type silver-germanium sulfide ore. In the contact area between adjacent main grains, a grain boundary control phase extending along the grain boundary can be seen. A small number of nanocrystalline contrast regions are also distributed inside the control phase, indicating that the added grain boundary ion channel control component forms a grain boundary control phase in the grain contact zone after composite sintering. This grain boundary control phase can fill part of the grain gaps, increase the effective contact area, and help reduce the total impedance of the electrolyte sheet.

[0042] like Figure 4As shown, the curve is a vertical crossing Figure 3 The representative EDS line scan results at the grain boundary center are shown, with the intensity of each element normalized. A significant relative intensity peak for iodine appears in the grain boundary center region, while the relative intensity of chlorine decreases, sulfur decreases, and phosphorus remains continuously distributed. This indicates that iodine is not uniformly dissolved in the Li6PS5Cl main grains, but is relatively enriched in the grain boundary control phase. This elemental distribution supports the formation of an iodine-containing thiophosphate grain boundary control phase in the contact region of the main grains after composite sintering.

[0043] Example 2

[0044] Preparation of grain boundary ion channel modulating components: Weigh out 50.0g of lithium sulfide, 80.0g of phosphorus pentasulfide, 5.00g of lithium iodide, and 1.50g of lithium phosphate, totaling 136.50g. Add the above raw materials and zirconia grinding balls to a 4L sealed zirconia ball mill jar. The mass ratio of zirconia grinding balls to raw materials is 25:1, i.e., the mass of the grinding balls is 3412.5g. Set the ball mill speed to 400r / min and ball mill continuously for 20min, then stop for 15min, for a total ball milling time of 12h (including the stop time). During the ball milling process, maintain the outer wall temperature of the ball mill jar between 20-32℃. After ball milling, remove the mixture to obtain a mechanically activated mixture.

[0045] The mechanically activated mixture was heated to 200°C at a heating rate of 2°C / min under an argon atmosphere and held at that temperature for 5 hours, followed by a cooling rate of 1°C / min to room temperature. The heat-treated product was ground for 5 minutes and passed through a 200-mesh standard sieve to obtain the grain boundary ion channel regulating component. The particle size D of this grain boundary ion channel regulating component was measured. 50 Its thickness is 1.2 μm, and its specific surface area is 11.2 m². 2 / g.

[0046] Preparation of sulfide solid electrolytes: Weigh out 50.0 g of lithium sulfide, 47.50 g of phosphorus pentasulfide, 16.50 g of lithium chloride, and 2.50 g of the aforementioned grain boundary ion channel regulating component, for a total mass of 116.50 g. Add the above raw materials and zirconia grinding balls to a 4 L sealed zirconia ball milling jar. The mass ratio of zirconia grinding balls to raw materials is 30:1, i.e., the mass of the grinding balls is 3495.0 g. Set the ball milling speed to 450 r / min and ball milling is carried out in a cycle of continuous ball milling for 25 min followed by a 15 min stop, for a total ball milling time of 18 h (including the stop time). During the ball milling process, the temperature of the outer wall of the ball milling jar is maintained at 22-40℃. After ball milling, remove the mixture to obtain the solid electrolyte precursor.

[0047] The solid electrolyte precursor was loaded into a covered boron nitride crucible, which was then placed in a sealed stainless steel reaction vessel. The vessel was evacuated to an absolute pressure of 40 Pa and then filled with 99.999% pure argon gas until the gauge pressure reached 0.020 MPa. The temperature was increased to 470 °C at a heating rate of 2 °C / min and held for 8 h. The mixture was then cooled to room temperature at a cooling rate of 1 °C / min. The sintered material was ball-milled at 250 r / min for 3 h and passed through a 100-mesh standard sieve (150 μm pore size) to obtain the sulfide solid electrolyte. The particle size D was measured. 50 The particle size is 2.8 μm, and the particle size D is... 90 It is 10.5μm.

[0048] Example 3

[0049] Preparation of grain boundary ion channel modulating components: Weigh out 50.0g of lithium sulfide, 83.0g of phosphorus pentasulfide, 7.50g of lithium iodide, and 2.50g of lithium phosphate, totaling 143.00g. Add the above raw materials and zirconia grinding balls to a 4L sealed zirconia ball mill jar. The mass ratio of zirconia grinding balls to raw materials is 35:1, i.e., the mass of grinding balls is 5005.0g. Set the ball mill speed to 500r / min and ball mill continuously for 30min, then stop for 10min, for a total ball milling time of 8h (including downtime). During the ball milling process, maintain the outer wall temperature of the ball mill jar at 30-45℃. After ball milling, remove the mixture to obtain a mechanically activated mixture.

[0050] The mechanically activated mixture was heated to 230°C at a heating rate of 5°C / min under an argon atmosphere and held at that temperature for 3 hours, followed by a cooling rate of 3°C / min to room temperature. The heat-treated product was ground for 5 minutes and passed through a 200-mesh standard sieve to obtain the grain boundary ion channel regulating component. The particle size D of this grain boundary ion channel regulating component was measured. 50 Its thickness is 2.3 μm, and its specific surface area is 6.8 m². 2 / g.

[0051] Preparation of sulfide solid electrolytes: Weigh out 50.0g of lithium sulfide, 50.0g of phosphorus pentasulfide, 18.50g of lithium chloride, and 4.00g of the aforementioned grain boundary ion channel regulating component, for a total mass of 122.50g. Add the above raw materials and zirconia grinding balls to a 4L sealed zirconia ball milling jar. The mass ratio of zirconia grinding balls to raw materials is 40:1, i.e., the mass of the grinding balls is 4900.0g. Set the ball milling speed to 600r / min and ball milling is carried out in a cycle of continuous ball milling for 35min followed by a 10min stop, for a total ball milling time of 10h (including the stop time). During the ball milling process, the temperature of the outer wall of the ball milling jar is maintained at 35-50℃. After ball milling, remove the mixture to obtain a solid electrolyte precursor.

[0052] The solid electrolyte precursor was loaded into a covered boron nitride crucible, which was then placed in a sealed stainless steel reaction vessel. The vessel was evacuated to an absolute pressure of 25 Pa and then filled with 99.999% pure argon gas until the gauge pressure reached 0.050 MPa. The temperature was increased to 520 °C at a rate of 4 °C / min and held for 4 h. The mixture was then cooled to room temperature at a rate of 3 °C / min. The sintered material was ball-milled at 400 r / min for 1 h and passed through a 300-mesh standard sieve (48 μm pore size) to obtain the sulfide solid electrolyte. The particle size D was measured. 50 The particle size is 4.2 μm, and the particle size D is... 90 It is 13.8 μm.

[0053] Example 4

[0054] Preparation of grain boundary ion channel modulating components: Weigh out 50.0g of lithium sulfide, 81.5g of phosphorus pentasulfide, 7.5g of lithium iodide, and 2.50g of lithium phosphate, totaling 141.50g. Add the above raw materials and zirconia grinding balls to a 4L sealed zirconia ball mill jar. The mass ratio of zirconia grinding balls to raw materials is 30:1, i.e., the mass of grinding balls is 4245.0g. Set the ball mill speed to 450r / min and ball milling is carried out in a cycle of 25min continuous ball milling followed by 12min stop ball milling, for a total ball milling time of 10h (including stop time). During the ball milling process, the temperature of the outer wall of the ball mill jar is maintained at 24-36℃. After ball milling, remove the mixture to obtain a mechanically activated mixture.

[0055] The mechanically activated mixture was heated to 215°C at a heating rate of 3°C / min under an argon atmosphere and held at that temperature for 4 hours, followed by a cooling rate of 2°C / min to room temperature. The heat-treated product was ground for 5 minutes and passed through a 200-mesh standard sieve to obtain the grain boundary ion channel regulating component. The particle size D of this grain boundary ion channel regulating component was measured. 50 Its thickness is 1.6 μm, and its specific surface area is 9.3 m². 2 / g.

[0056] Preparation of sulfide solid electrolytes: Weigh out 50.0 g of lithium sulfide, 48.75 g of phosphorus pentasulfide, 17.50 g of lithium chloride, and 3.25 g of the aforementioned grain boundary ion channel regulating component, for a total mass of 119.50 g. Add the above raw materials and zirconia grinding balls to a 4 L sealed zirconia ball milling jar. The mass ratio of zirconia grinding balls to raw materials is 35:1, i.e., the mass of the grinding balls is 4182.5 g. Set the ball milling speed to 525 r / min and ball milling is carried out in a cycle of 30 min continuous ball milling followed by 12 min stop ball milling, for a total ball milling time of 14 h (including stop time). During the ball milling process, the temperature of the outer wall of the ball milling jar is maintained at 27-43℃. After ball milling, remove the mixture to obtain a solid electrolyte precursor.

[0057] The solid electrolyte precursor was loaded into a covered boron nitride crucible, which was then placed in a sealed stainless steel reaction vessel. The vessel was evacuated to an absolute pressure of 30 Pa and then filled with 99.999% pure argon gas until the gauge pressure reached 0.035 MPa. The temperature was increased to 495 °C at a rate of 3 °C / min and held for 6 h. The mixture was then cooled to room temperature at a rate of 2 °C / min. The sintered material was ball-milled at 325 r / min for 2 h and passed through a 200-mesh standard sieve to obtain the sulfide solid electrolyte. The particle size D was measured. 50 The particle size is 3.2 μm, and the particle size D is... 90 It is 11.8 μm.

[0058] Example 5

[0059] Preparation of grain boundary ion channel modulating components: The preparation method is exactly the same as that of the grain boundary ion channel regulation component in Example 1, using the same raw material ratio and process parameters.

[0060] Preparation of sulfide solid electrolytes: Weigh out 50.0 g of lithium sulfide, 48.75 g of phosphorus pentasulfide, 17.50 g of lithium chloride, and 3.25 g of the aforementioned grain boundary ion channel regulating component, for a total mass of 119.50 g. Add the above raw materials and zirconia grinding balls to a 4 L sealed zirconia ball milling jar. The mass ratio of zirconia grinding balls to raw materials is 35:1, i.e., the mass of the grinding balls is 4182.5 g. Set the ball milling speed to 525 r / min and ball milling is carried out in a cycle of 30 min continuous ball milling followed by 12 min stop ball milling, for a total ball milling time of 14 h (including stop time). During the ball milling process, the temperature of the outer wall of the ball milling jar is maintained at 26-44℃. After ball milling, remove the mixture to obtain a solid electrolyte precursor.

[0061] The solid electrolyte precursor was loaded into a covered boron nitride crucible, which was then placed in a sealed stainless steel reaction vessel. After evacuating to an absolute pressure of 28 Pa, 99.999% pure argon gas was introduced until the gauge pressure reached 0.035 MPa. The reaction vessel was placed in a tube furnace, and a two-stage heating process was employed: first, the temperature was increased to 275 °C at a rate of 3 °C / min and held for 1.5 h; then, it was increased to 495 °C at a rate of 2.5 °C / min and held for 6 h; finally, it was cooled to room temperature at a rate of 2 °C / min. The sintered material was ball-milled at 325 r / min for 2 h and passed through a 200-mesh standard sieve to obtain the sulfide solid electrolyte. The particle size D was measured. 50 The particle size is 3.3 μm, and the particle size D is... 90 It is 12.0 μm.

[0062] Comparative Example 1 Li6PS5Cl matrix electrolyte without added grain boundary ion channel modulators: Weigh out 50.0g of lithium sulfide, 48.75g of phosphorus pentasulfide, and 17.50g of lithium chloride, totaling 116.25g. Add the above raw materials and zirconia grinding balls to a 4L sealed zirconia ball milling jar. The mass ratio of zirconia grinding balls to raw materials is 35:1, i.e., the mass of the grinding balls is 4068.8g. Set the ball milling speed to 525r / min and ball milling is carried out in a cycle of 30min continuous ball milling followed by 12min stop ball milling, for a total ball milling time of 14h (including stop time). During the ball milling process, the temperature of the outer wall of the ball milling jar is maintained between 27-44℃. After ball milling, remove the mixture to obtain a solid electrolyte precursor.

[0063] The solid electrolyte precursor was loaded into a covered boron nitride crucible, which was then placed in a sealed stainless steel reaction vessel. The vessel was evacuated to an absolute pressure of 32 Pa and then filled with 99.999% pure argon gas until the gauge pressure reached 0.035 MPa. The temperature was increased to 495 °C at a rate of 3 °C / min and held for 6 h. The mixture was then cooled to room temperature at a rate of 2 °C / min. The sintered material was ball-milled at 325 r / min for 2 h and passed through a 200-mesh standard sieve to obtain the sulfide solid electrolyte. The particle size D was measured. 50 The particle size is 3.8 μm, and the particle size D is... 90 It is 14.5μm.

[0064] Comparative Example 2 Sulfide solid electrolytes using lithium bromide in equimolar replacement of lithium chloride: The preparation of the grain boundary ion channel regulating component was exactly the same as in Example 1.

[0065] Preparation of sulfide solid electrolytes: Weigh out 50.0 g of lithium sulfide, 48.75 g of phosphorus pentasulfide, 35.84 g of lithium bromide, and 3.25 g of the grain boundary ion channel regulating component obtained in Example 1, for a total mass of 137.84 g. The amount of lithium bromide is the same as that of lithium chloride in Example 1 (17.50 g ÷ 42.39 g / mol = 0.4128 mol, 0.4128 mol × 86.85 g / mol = 35.84 g). Add the above raw materials and zirconia grinding balls to a 4 L sealed zirconia ball mill jar. The mass ratio of zirconia grinding balls to raw materials is 35:1, i.e., the mass of the grinding balls is 4824.4 g. Set the ball mill speed to 525 r / min and ball milling is carried out in a cycle of 30 min continuous ball milling followed by 12 min stop ball milling, for a total ball milling time of 14 h (including stop time). During the ball milling process, the outer wall temperature of the ball mill jar is maintained at 29-46 °C. After ball milling, the mixture was removed to obtain a solid electrolyte precursor.

[0066] The solid electrolyte precursor was loaded into a covered boron nitride crucible, which was then placed in a sealed stainless steel reaction vessel. The vessel was evacuated to an absolute pressure of 35 Pa and then filled with 99.999% pure argon gas until the gauge pressure reached 0.035 MPa. The temperature was increased to 495 °C at a rate of 3 °C / min and held for 6 h. The mixture was then cooled to room temperature at a rate of 2 °C / min. The sintered material was ball-milled at 325 r / min for 2 h and passed through a 200-mesh standard sieve to obtain the sulfide solid electrolyte. The particle size D was measured. 50 The particle size is 4.5 μm, and the particle size D is... 90 It is 16.2 μm.

[0067] Comparative Example 3 Sulfide solid electrolytes without lithium iodide and lithium phosphate in the grain boundary ion channel regulation component: Preparation of grain boundary ion channel modulating components: Weigh out 50.0g of lithium sulfide and 81.5g of phosphorus pentasulfide, for a total mass of 131.5g. Add the above raw materials and zirconia grinding balls to a 4L sealed zirconia ball mill jar. The mass ratio of zirconia grinding balls to raw materials is 30:1, i.e., the mass of the grinding balls is 3945.0g. Set the ball mill speed to 450r / min and ball milling is carried out in a cycle of 25min continuous ball milling followed by 12min stop ball milling, for a total ball milling time of 10h (including stop time). During the ball milling process, the temperature of the outer wall of the ball mill jar is maintained at 24-37℃. After ball milling, remove the mixture to obtain a mechanically activated mixture.

[0068] The mechanically activated mixture was heated to 215°C at a heating rate of 3°C / min under an argon atmosphere and held at that temperature for 4 hours, followed by a cooling rate of 2°C / min to room temperature. The heat-treated product was ground for 5 minutes and passed through a 200-mesh standard sieve to obtain the grain boundary regulating component. The particle size D of this grain boundary regulating component was tested. 50 Its thickness is 2.5 μm, and its specific surface area is 5.2 m². 2 / g.

[0069] Preparation of sulfide solid electrolytes: Weigh out 50.0 g of lithium sulfide, 48.75 g of phosphorus pentasulfide, 17.50 g of lithium chloride, and 3.25 g of the aforementioned grain boundary regulating component, for a total mass of 119.50 g. Add the above raw materials and zirconia grinding balls to a 4 L sealed zirconia ball milling jar. The mass ratio of zirconia grinding balls to raw materials is 35:1, i.e., the mass of the grinding balls is 4182.5 g. Set the ball milling speed to 525 r / min and ball milling is carried out in a cycle of 30 min continuous ball milling followed by 12 min stop ball milling, for a total ball milling time of 14 h (including stop time). During the ball milling process, the temperature of the outer wall of the ball milling jar is maintained at 28-44℃. After ball milling, remove the mixture to obtain a solid electrolyte precursor.

[0070] The solid electrolyte precursor was loaded into a covered boron nitride crucible, which was then placed in a sealed stainless steel reaction vessel. The vessel was evacuated to an absolute pressure of 30 Pa and then filled with 99.999% pure argon gas until the gauge pressure reached 0.035 MPa. The temperature was increased to 495 °C at a rate of 3 °C / min and held for 6 h. The mixture was then cooled to room temperature at a rate of 2 °C / min. The sintered material was ball-milled at 325 r / min for 2 h and passed through a 200-mesh standard sieve to obtain the sulfide solid electrolyte. The particle size D was measured. 50 The particle size is 3.6 μm, and the particle size D is... 90 It is 12.8 μm.

[0071] Comparative Example 4 The grain boundary ion channel modulation component uses 550℃ high-temperature sintering instead of 200-230℃ heat-treated sulfide solid electrolyte: Preparation of grain boundary ion channel modulating components: Weigh out 50.0g of lithium sulfide, 81.5g of phosphorus pentasulfide, 6.25g of lithium iodide, and 2.00g of lithium phosphate, totaling 139.75g. Add the above raw materials and zirconia grinding balls to a 4L sealed zirconia ball mill jar. The mass ratio of zirconia grinding balls to raw materials is 30:1, i.e., the mass of grinding balls is 4192.5g. Set the ball mill speed to 450r / min and ball milling is carried out in a cycle of 25min continuous ball milling followed by 12min stop ball milling, for a total ball milling time of 10h (including stop time). During the ball milling process, the temperature of the outer wall of the ball mill jar is maintained between 26-39℃. After ball milling, remove the mixture to obtain a mechanically activated mixture.

[0072] The mechanically activated mixture was heated to 550°C at a heating rate of 3°C / min under an argon atmosphere and held at that temperature for 4 hours, followed by a cooling rate of 2°C / min to room temperature. The heat-treated product was ground for 5 minutes and passed through a 200-mesh standard sieve to obtain the grain boundary regulating component. The particle size D of this grain boundary regulating component was measured. 50 Its thickness is 3.8 μm, and its specific surface area is 2.1 m². 2 / g.

[0073] Preparation of sulfide solid electrolytes: Weigh out 50.0g of lithium sulfide, 48.75g of phosphorus pentasulfide, 17.50g of lithium chloride, and 3.25g of the aforementioned grain boundary regulating component, for a total mass of 119.50g. Add the above raw materials and zirconia grinding balls to a 4L sealed zirconia ball milling jar. The mass ratio of zirconia grinding balls to raw materials is 35:1, meaning the mass of the grinding balls is 4182.5g. Set the ball milling speed to 525r / min and perform ball milling in a cycle of 30min continuous milling followed by a 12min pause, for a total milling time of 14h (including pauses). During the milling process, maintain the outer wall temperature of the ball milling jar between 27-45℃. After milling, remove the mixture to obtain the solid electrolyte precursor.

[0074] The solid electrolyte precursor was loaded into a covered boron nitride crucible, which was then placed in a sealed stainless steel reaction vessel. The vessel was evacuated to an absolute pressure of 30 Pa and then filled with 99.999% pure argon gas until the gauge pressure reached 0.035 MPa. The temperature was increased to 495 °C at a rate of 3 °C / min and held for 6 h. The mixture was then cooled to room temperature at a rate of 2 °C / min. The sintered material was ball-milled at 325 r / min for 2 h and passed through a 200-mesh standard sieve to obtain the sulfide solid electrolyte. The particle size D was measured. 50 The particle size is 4.0 μm, and the particle size D is... 90 It is 14.1 μm.

[0075] Summary of Performance Test Results for Examples The following performance tests were performed on the sulfide solid electrolytes obtained in Examples 1-5 and Comparative Examples 1-4.

[0076] 1. Lithium-ion conductivity and lithium-ion activation energy testing: Electrolyte powders were pressed into sheet-like samples with a diameter of 10 mm and a thickness of approximately 1.5 mm under a pressure of 300 MPa. Gold electrodes were sputtered onto both sides, and the samples were maintained at an external pressure of 300 MPa during the testing process. AC impedance spectroscopy was measured using an electrochemical workstation (Bio-Logic VMP-300) at a constant temperature of 25 °C, with a frequency range of 7 MHz to 0.1 Hz and an AC amplitude of 10 mV. The total resistance R of the electrolyte sheet was obtained by equivalent circuit fitting, and the lithium-ion conductivity was calculated using the formula σ = L / (R × A) based on the measured thickness L of the sheet-like sample and the effective area A of the gold electrode. This fitting was only used to extract the total resistance and did not quantify the bulk resistance and grain boundary resistance separately. AC impedance spectra were measured at 10, 15, 20, 25, 30, 35, and 40 °C, and the lithium-ion conduction activation energy Ea was obtained by fitting the Arrhenius equation σ = σ0 × exp(−Ea / kT). All samples were prepared under the same conditions and under continuous external pressure. The data in Table 1 are used to compare the trends of overall conductivity and total impedance.

[0077] Table 1. Lithium-ion conductivity and activation energy of sulfide solid electrolytes in each example and comparative example.

[0078] As shown in Table 1, the lithium-ion conductivity of Examples 1-5 is not lower than 3.5 mS / cm, and the lithium-ion activation energy is not higher than 0.32 eV. Specifically, using the formulation of Example 1, the lithium-ion conductivity reaches 5.2 mS / cm, and the activation energy is 0.28 eV; using the formulation of Example 2, with a smaller amount of grain boundary ion channel regulating component added, the conductivity is 4.1 mS / cm; using the formulation of Example 3, with an increased amount of regulating component and a corresponding decrease in the relative proportion of the main crystalline phase raw material, the conductivity is 4.8 mS / cm; in Example 4, after adjusting the ratio of lithium iodide and lithium phosphate, the conductivity is 4.6 mS / cm; in Example 5, using a two-stage heating process, the conductivity reaches 5.5 mS / cm, indicating that the pre-heating step is beneficial for homogenizing the precursor reaction. A comparison of the lithium-ion conductivity and activation energy of each example and comparative example is shown in Table 1.

[0079] Comparative Example 1, without the addition of grain boundary ion channel regulating components, exhibited a lithium-ion conductivity of 2.8 mS / cm and a conduction activation energy of 0.36 eV, indicating that direct contact and gaps between grains increased the total impedance of the electrolyte sheet. Comparative Example 2, using lithium bromide to replace lithium chloride in equimolar amounts, transformed the main crystalline phase into Li6PS5Br with residual LiBr, reducing the conductivity to 1.2 mS / cm. Comparative Example 3, without the addition of lithium iodide and lithium phosphate in its grain boundary regulating components, showed incomplete nanocrystalline-amorphous interconnect features in representative TEM fields, with a conductivity of 3.2 mS / cm. Comparative Example 4, prepared using a grain boundary regulating component at 550℃, exhibited high crystallinity and lost significant nanocrystalline-amorphous interconnect features, resulting in an electrolyte conductivity of 3.0 mS / cm. These results demonstrate that the structural characteristics and formulation of the pre-prepared regulating components play a role in reducing the total impedance of the electrolyte sheet.

[0080] 2. Electrochemical Window Test (LSV): The electrochemical window of the electrolyte was determined using linear sweep voltammetry. A stainless steel sheet was used as the working electrode, and a lithium sheet was used as both the counter and reference electrodes. The electrolyte layer thickness was 0.5 mm, and the scan rate was 0.1 mV / s, scanning from the open-circuit potential forward to 5.0 V (vs. Li / Li). + With a current density reaching 0.1 mA / cm² 2 The corresponding potential is taken as the oxidative decomposition initiation potential. The test results are shown in Table 2.

[0081] Table 2 Electrochemical windows for each example and comparative example

[0082] As shown in Table 2, the oxidation decomposition initiation potentials of all embodiments are higher than those of the comparative examples. Example 5, employing a two-stage heating process, had an oxidation decomposition initiation potential of 2.85V; Comparative Example 2, due to the transformation of the main crystalline phase to Li6PS5Br accompanied by residual phases, had an oxidation decomposition initiation potential of 2.45V. The results in Table 2 are only used to compare the oxidation decomposition initiation trends of the electrolytes under the same LSV test conditions.

[0083] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. A sulfide solid electrolyte, characterized in that, It is made from raw materials comprising the following parts by weight: 100 parts lithium sulfide, 94-100 parts phosphorus pentasulfide, 33-39 parts lithium chloride, and 4-10 parts grain boundary ion channel regulating components. The grain boundary ion channel regulating component is made from raw materials comprising the following parts by weight: 100 parts lithium sulfide, 160-166 parts phosphorus pentasulfide, 8-18 parts lithium iodide and 2-6 parts lithium phosphate. The grain boundary ion channel regulating component has a nanocrystalline-amorphous interconnect structure composed of β-Li3PS4 nanocrystalline domains and an amorphous intergranular phase located between adjacent β-Li3PS4 nanocrystalline domains; the amorphous intergranular phase is a Li2S-P2S5 amorphous glass phase containing lithium iodide and lithium phosphate, and lithium iodide and lithium phosphate are jointly distributed in the amorphous intergranular phase. The sulfide solid electrolyte has a Li6PS5Cl type silver-germanium sulfide main crystal phase. The grain boundary ion channel regulating component forms an iodine-containing thiophosphate grain boundary regulating phase after composite sintering. The grain boundary regulating phase is distributed in the grain contact region of the Li6PS5Cl type silver-germanium sulfide main crystal phase.

2. The sulfide solid electrolyte according to claim 1, characterized in that, The sulfide solid electrolyte is made from raw materials comprising the following parts by weight: 100 parts lithium sulfide, 95-100 parts phosphorus pentasulfide, 33-37 parts lithium chloride, and 5-8 parts grain boundary ion channel regulating components.

3. The sulfide solid electrolyte according to claim 1, characterized in that, The grain boundary ion channel regulating component is made from raw materials comprising the following parts by weight: 100 parts lithium sulfide, 160-166 parts phosphorus pentasulfide, 10-15 parts lithium iodide, and 3-5 parts lithium phosphate.

4. The sulfide solid electrolyte according to claim 1, characterized in that, The purity of the lithium sulfide is not less than 99.9%; The purity of the phosphorus pentasulfide is not less than 99.9%; The purity of the lithium chloride, lithium iodide, and lithium phosphate shall not be less than 99.5%.

5. The sulfide solid electrolyte according to claim 1, characterized in that, The particle size D of the grain boundary ion channel regulating component 50 Its thickness is 0.5-3.0 μm, and its specific surface area is 3-15 m². 2 / g; the particle size D of the sulfide solid electrolyte 50 The particle size is 1-8 μm, and the particle size D 90 No larger than 15μm.

6. The sulfide solid electrolyte according to claim 1, characterized in that, The X-ray diffraction pattern of the sulfide solid electrolyte shows that the Li6PS5Cl type silver-germanium sulfide phase is the main crystalline phase, and there are β-Li3PS4 related crystalline phase characteristics and amorphous scattering background. The lithium-ion conductivity of the sulfide solid electrolyte measured at 25℃ and 300MPa is not less than 3.5mS / cm, and the lithium-ion conduction activation energy is not higher than 0.32eV.

7. A method for preparing the sulfide solid electrolyte according to any one of claims 1-6, characterized in that, Includes the following steps: S1. In an argon-protected environment with a water content not exceeding 0.1 ppm and an oxygen content not exceeding 0.1 ppm, weigh the raw materials according to the following proportions: 100 parts by mass of lithium sulfide, 160-166 parts by mass of phosphorus pentasulfide, 8-18 parts by mass of lithium iodide, and 2-6 parts by mass of lithium phosphate. Add the raw materials and zirconium oxide grinding media to a closed ball mill container, control the mass ratio of grinding media to raw materials to be 25:1-35:1, and ball mill at 400-500 r / min for 8-12 h to obtain a mechanically activated mixture. S2. The mechanically activated mixture is placed in an argon atmosphere and heated to 200-230°C at a heating rate of 2-5°C / min and held at that temperature for 3-5 hours. Then, it is cooled to below 80°C at a cooling rate of 1-3°C / min, ground, and passed through a 200-mesh sieve to obtain a grain boundary ion channel regulating component with a β-Li3PS4 nanocrystalline-amorphous interconnection structure. S3. Weigh the raw materials according to 100 parts by mass of lithium sulfide, 94-100 parts by mass of phosphorus pentasulfide, 33-39 parts by mass of lithium chloride and 4-10 parts by mass of the grain boundary ion channel regulating component. Add the raw materials and zirconium oxide grinding media into a closed ball mill container, control the mass ratio of grinding media to raw materials to be 30:1-40:1, and ball mill at 450-600 r / min for 10-18 h to obtain a solid electrolyte precursor. S4. The solid electrolyte precursor is loaded into a covered boron nitride crucible, and the boron nitride crucible is placed in a sealed stainless steel reaction vessel. The sealed stainless steel reaction vessel is evacuated and purged with argon gas 2-3 times. Finally, the vacuum is evacuated to an absolute pressure not higher than 50 Pa, and then argon gas with a purity not lower than 99.999% is introduced to a gauge pressure of 0.02-0.05 MPa. The temperature is increased to 470-520℃ at a heating rate of 2-4℃ / min and held for 4-8 hours. The temperature is then cooled to below 80℃ at a cooling rate of 1-3℃ / min to obtain a sinter containing the main crystalline phase of Li6PS5Cl type silver sulfide germanium ore. S5. In the argon-protected environment, the sinter is ball-milled with zirconia grinding balls as the grinding medium at 250-400 r / min for 1-3 h, and then passed through a 100-300 mesh sieve to obtain the sulfide solid electrolyte. The ball-milling time in each of the above steps is the total time including the pause time.

8. The preparation method according to claim 7, characterized in that, The ball milling in step S1 is carried out in a cycle of continuous ball milling for 20-30 minutes and stopping ball milling for 10-15 minutes. During the ball milling process, the outer wall temperature of the sealed ball milling container is maintained at 20-45℃.

9. The preparation method according to claim 7, characterized in that, The ball milling in step S3 is carried out in a cycle of continuous ball milling for 25-35 minutes and stopping ball milling for 10-15 minutes. During the ball milling process, the outer wall temperature of the sealed ball milling container is maintained at 20-50℃.

10. The preparation method according to claim 7, characterized in that, Step S4 includes: first heating to 250-300℃ at a heating rate of 2-4℃ / min and holding for 1-2 hours, then heating to 470-520℃ at a heating rate of 2-3℃ / min and holding for 4-8 hours; the sulfide solid electrolyte obtained in step S5 is sealed and packaged in a dry argon atmosphere with a dew point not higher than -60℃.

Citation Information

Patent Citations

  • Argyrodite type sulfide lithium ion solid electrolyte and preparation method and application thereof

    CN113937351A

  • KR20240080507A